Comparison of matrix converter stabilisation techniques based on the damping resistor and digital filter approaches for bidirectional power flow control. Issue 15 (13th November 2019) - Malekjamshidi, Zahra; Jafari, Mohammad; Zhu, Jianguo; Xiao, Dan
Abstract : The matrix converter is becoming a mature technology with its specific advantages and limitations and can be effectively used as interface link in the future smart grids. In this context, the stability of the converter under different power flow conditions is highly important and needs more clarification. The input inductor–capacitor filter can significantly impact the stability of the converter when the output is tightly regulated, especially in bidirectional power flow control applications where a low‐impedance source is connected to the converter output. This study investigates the matrix converter stability for bidirectional power flow control, considering the input filter and other parameters of the system. A detailed analysis of two commonly used active and passive stabilisation techniques known as digital filter and damping resistor approaches is presented, and a combination of these two methods is suggested as a better choice. The converter stability region for the proposed technique is determined by using the small‐signal model of the converter. The converter performance for the methods is compared in terms of the efficiency, stability, transients, and quality of the input and output currents. Numerical simulations and experimental tests are conducted on a prototype direct matrix converter to validate the proposed method.